COMPARATIVE STATISTICAL ANALYSIS OF VEGETABLE AGRICULTURAL PRODUCTION IN ROMANIA IN THE PERIOD 2009-2021 - Ramona-Maria DIMITROV (Management & Marketing)
In this paper, a statistical analysis of vegetable agricultural production in Romania is made in the period 2009-2021 and a comparative study is carried out regarding the average productions per hectare for certain crops obtained at S.C.D.A. Simnic, respectively in Dolj county and at the national level. It is thus found that there are no significant differences between the average productions per hectare for wheat, sunflower, barley and pea crops from a statistical point of view, at a significance level of 5%. On the other hand, the level of average production per hectare of corn silage and colza in the period 2009-2021 at the S.C.D.A Simnic is significantly lower than at the national level. Comparing the average agricultural production per hectare of oats, it is found that at S.C.D.A Simnic it is significantly higher than the average production obtained in Dolj county and the national level. The work ends with recommendations regarding production management and measures to optimize it.